Leadership that matters : the critical factors for making a difference in people's lives and organizations' success - Sashkin, Marshall, 1944-; Sashkin, Molly G (San Francisco : Berrett-Koehler, 2003)
'Leadership That Matters examines transformational leadership - leadership that not only improves productivity and performance but also makes a positive difference in the lives of organization members. Transformational leaders achieve superior results because of their ability to transform people from dutiful followers into self-directed leaders who go beyond simply doing what is expected of them.''Drawing on research that investigates leadership, culture, and performance in dozens of organizations, the Sashkins describe the specific behaviors and personal characteristics of transformational leaders. They show how you can construct an empowering organizational culture that nurtures self-reliance and long-term thinking. They offer practical advice on how you can become a transformational leader - and make leadership matter.'--BOOK JACKET
What is leadership? -- What have we learned about leadership? -- Leadership skills and behaviors -- Charisma and character -- Leaders, followers, and power -- Leaders with the confidence to act -- Vision : how leaders think -- Leadership in context -- How transformational leaders construct the cultural context -- Six paradoxes of leadership : transforming followers -- How do we know leadership matters? : the research evidence -- Issues in leadership : implications for transformational leaders -- Leadership that matters : a new synthesis -- Appendix one : bibliography -- Appendix two : development of The Leadership Profile
Includes bibliographical references (p. 211-230) and index
Koleksi Sumbangan : Prof. Datuk (Dr. ) Anuwar Ali
Keywords: Leadership